Front Cover Image. Issue 2 (10th February 2021) - Zhao, Xin‐Gang; Shi, Zhiming; Wang, Xinjiang; Zou, Hongshuai; Fu, Yuhao; Zhang, Lijun
Abstract : The easy transferability and feasible epitaxial growth of two‐dimensional semiconductors pave a promising way to further tune their optoelectronic properties by constructing van der Waals heterostructures. The authors herein performed a high‐throughput first‐principles study of electronic structure and optical properties of the layer‐by‐layer stacking heterostructing superlattices of two‐dimensional transition metal dichalcogenides. The indirect‐to‐direct band‐gap transition or even semiconductor‐to‐metal transition can be realized by varying component compositions of superlattices. The results provide useful guidance for engineering optoelectronic properties by forming heterostructures and superlattices in two‐dimensional semiconductors. (DOI: 10.1002/inf2.12155 ) Abstract : The easy transferability and feasible epitaxial growth of two‐dimensional semiconductors pave a promising way to further tune their optoelectronic properties by constructing van der Waals heterostructures. The authors herein performed a high‐throughput first‐principles study of electronic structure and optical properties of the layer‐by‐layer stacking heterostructing superlattices of two‐dimensional transition metal dichalcogenides. The indirect‐to‐direct band‐gap transition or even semiconductor‐to‐metal transition can be realized by varying component compositions of superlattices. The results provide useful guidance for engineering optoelectronic properties by forming heterostructures and superlattices in two‐dimensional semiconductors. (DOI: 10.1002/inf2.12155 )